Pandemic State Failure, Hydrocarbon Control, and Indigenous Territorial Counteraction in the Peruvian Amazon - Watson, Ana; Davidsen, Conny (Frontiers in Human Dynamics, 2021)
During the COVID-19 pandemic, the national government failed to protect its sparsely populated Amazon region. While infections were still rising, resource extraction was quickly approved to continue operations as a declared essential service that permitted an influx of workers into vulnerable indigenous territories despite weak or almost absent local health care. This paper analyzes territorial counter-action as an indigenous response to pandemic national state failure, highlighted in a case of particularly conflictive stakes of resource control: Peru’s largest liquid natural gas extraction site Camisea in the Upper Amazon, home to several indigenous groups in the Lower Urubamba who engaged in collective action to create their own district. Frustration with the state’s handling of the crisis prompted indigenous counter-action to take COVID-19 measures and territorial control into their own hands. By blocking boat traffic on their main river, they effectively cut off their remote and roadless Amazon district off from the outside world. Local indigenous control had already been on the rise after the region had successfully fought for its own formal sub-national administrative jurisdiction in 2016, named Megantoni District. The pandemic then created a moment of full indigenous territorial control that openly declared itself as a response and replacement of a failed national state. Drawing on political ecology, we analyze this as an interesting catalyst moment that elevated long-standing critiques of inequalities and state neglect into new negotiations of territory and power between the state and indigenous self-determination, with potentially far-reaching implications on state-indigenous power dynamics, and territorial control, beyond the pandemic.